Study of Flue Gas Pollutant Control in a 600 MW Coal-Fired Unit - Zhiyong ZHANG; Hua MO; Meng WANG; Wei SHUAI (Zhongguo dianli)
Taking a 600MW supercritical coal-fired unit as an example, the ultra-low emissions effect of W-flame boiler burning high sulfur, medium and high ash and low volatile coal was studied.The unit adopts the ultra-low emissions technology route of " selective non-catalytic reduction (SNCR)＋selective catalytic reduction (SCR) denitrification, double-chamber five-electric field electrostatic precipitator with high-frequency power supply+rotating electrode, and double-tower double-cycle wet-FGD system (3+5 layer spray)".According to Distributed Control System (DCS) and Continuous Emission Monitoring System (CEMS) data of the unit, NOx, particulate matter and SO2 concentrations at chimney outlet can reach ultra-low emission level stably.The SNCR device is in good operating condition. The ammonia escape of SCR device is large, and the maximum ammonia escape reaches 27.51mg/m3. The probability of exceeding the designed value of 2.28mg/m3 on side A and side B is 51.86% and 45.96%, respectively. The reason is that the concentration field of denitration system is unevenly distributed. The slurry density of desulfurization system is well controlled. The pH value of the slurry in the first tower is well controlled, but the pH value in the second tower is relatively low. The emission intensity of SO2, NOx and particulate matter is 48.7%, 7.7% and 28.9% lower than the national average emission intensity in 2019.